(untitled) (Research, Society and Development, 2020)
Considering the growing discussions about the insertion of topics of Modern and Contemporary Physics (MCP) in Basic Education and the research that deals with the formation of Physics teachers in these contents, a qualitative and quantitative research was developed, using a semi-structured questionnaire as a collection instrument of data, with all physics teachers in all public high schools (HS) in the city of Sobral - CE, who graduated after the year 2002, totaling 15 teachers in 13 schools, aiming to discuss and analyze the aspects related to the teaching of these themes during the graduation of teachers, as well as their implications for HS. It was observed that: the difficulties they had in the study of these subjects during graduation are related to Mathematics; the most recurrent assessment tool was evidence; and that the mathematical aspect of MCP was the one most worked on by the teacher teachers, neglecting the conceptual, historical and experimental aspects of these subjects, for example. Regarding teaching, it was noticed that the class time that teachers have in the HS and the curriculum are the main obstacles faced by teacher.